Transfer Effects from Problem‐Solving Workshops to Negotiations: A Process and Outcome Model. Issue 4 (29th July 2020) - Fisher, Ronald J.
Abstract : The problem‐solving workshop (PSW) is a small‐group method of conflict analysis and resolution that is identified with the very origins of the field and that has a considerable history of theorizing and practice. Since the creation of the method, scholars have addressed the question of the transfer of outcomes and effects from workshops to negotiation, policy making, and political discourse. Following a definition and review of the intentions and rationale of transfer, a flow model is presented that consists of eight sequential components that capture the process and outcomes of transfer, in part by drawing on models of intervention and frameworks for the evaluation of PSWs. Notwithstanding the utility of this development, it is acknowledged that transfer is a very complex process whose evaluation entails significant constraints and whose ultimate and exact contributions to peace processes are likely unknowable.